2022
DOI: 10.3389/fphar.2022.857811
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Potentially Inappropriate Medication Use in Older Cancer Outpatients With Multimorbidity: Concordance Among the Chinese, AGS/Beers, and STOPP Criteria

Abstract: Objectives: Age-related multimorbidity is a general problem in older patients, which increases the prevalence of potentially inappropriate medication (PIM) use. This study aimed to examine the prevalence and predictors of PIM use in older Chinese cancer outpatients with multimorbidity based on the 2017 Chinese criteria, 2019 AGS/Beers criteria, and 2014 STOPP criteria.Methods: A cross-sectional study was conducted using electronic medical data from nine tertiary hospitals in Chengdu from January 2018 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
0
19
1
2
Order By: Relevance
“…The prevalence of PIM use in older lung cancer patients was higher than that in patients with the other two cancers according to the 2012 Beers criteria. The prevalence of PIM use, according to the 2019 Beers criteria, in our study was 37.28% over 3 years, which was higher than that reported in another study on the prevalence of PIM use among older Chinese cancer outpatients which were outside of palliative care and hospice service (32.65%; Tian et al, 2022a). Our previous study found that lung cancer was positively associated with PIM use in older cancer outpatients, which explains the higher prevalence of PIM use in this study.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of PIM use in older lung cancer patients was higher than that in patients with the other two cancers according to the 2012 Beers criteria. The prevalence of PIM use, according to the 2019 Beers criteria, in our study was 37.28% over 3 years, which was higher than that reported in another study on the prevalence of PIM use among older Chinese cancer outpatients which were outside of palliative care and hospice service (32.65%; Tian et al, 2022a). Our previous study found that lung cancer was positively associated with PIM use in older cancer outpatients, which explains the higher prevalence of PIM use in this study.…”
Section: Discussioncontrasting
confidence: 85%
“…Between 1999 and 2021, a total of 51 studies 11,[37][38][39][40][41][42][79][80][81][82][83][84][85][86][87][88][89][90][91][92]108,109 were performed in high-income countries, 23 studies [17][18][19][20][21][22][23][24][25][26][27][28][29]77,78,[93][94][95][96][97][98][99][100] in upper-to middle-income countries, 17 studies [30][31][32][33][34][35]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The study has proved that there was little difference between the 2017 Chinese and 2019 AGS/Beers criteria ( Tian et al, 2022 ), so the Beers criteria was also capable for Chinese. Our results are comparable to the PIM rate of ( Beezer et al, 2022 ), who reported that the incidence of PIM was 61.1% during hospitalization in older patients with heart failure.…”
Section: Discussionmentioning
confidence: 91%